2019
DOI: 10.1093/jbcr/irz055
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation Injury: Unmet Clinical Needs and Future Research

Abstract: Pulmonary and systemic insults from inhalation injury can complicate the care of burn patients and contribute to significant morbidity and mortality. However, recent progress in diagnosis and treatment of inhalation injury has not kept pace with the care of cutaneous thermal injury. There are many challenges unique to inhalation injury that have slowed advancement, including deficiencies in our understanding of its pathophysiology, the relative difficulty and subjectivity of bronchoscopic diagnosis, the lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 102 publications
0
11
0
2
Order By: Relevance
“…It predisposes the patient to secondary pneumonia and acute respiratory distress syndrome and often requires mechanical ventilation [ 41 ]. Currently, very little is known about airway microbiota after burn and inhalation injury [ 42 ].…”
Section: Reviewmentioning
confidence: 99%
“…It predisposes the patient to secondary pneumonia and acute respiratory distress syndrome and often requires mechanical ventilation [ 41 ]. Currently, very little is known about airway microbiota after burn and inhalation injury [ 42 ].…”
Section: Reviewmentioning
confidence: 99%
“…У пациентов, как правило, наблюдаются покраснение и припухлость ротоглотки, повышенная секреция слизи в дыхательных путях, появляется мокрота с примесью копоти, осиплость голоса. Это косвенные признаки отека дыхательных путей с последующей их обструкцией [8,9].…”
Section: механизмы ингаляционной травмыunclassified
“…В результате сочетанного воздействия теплового и химического факторов повреждающего агента и возникающих при этом вторичных эффектов возможно прямое повреждение паренхимы легких. Эти механизмы включают в себя: 1) повышение проницаемости сосудистой стенки с последующим отеком легких; 2) альвеолярный коллапс в результате отека легких; 3) повреждение клетки от АФК; 4) обструкция и окклюзия из-за продуктов горения и развившихся отеков; 5) снижение уровня поверхностно-активного вещества (ПАВ) (Поверхностно-акти́вные вещества́ (ПАВ) -химические соединения, которые, концентрируясь на поверхности раздела термодинамических фаз, вызывают снижение поверхностного натяжения); 6) формирование ателектазов; 7) снижение фагоцитоза макрофагами [9,8,13]. Вместе эти процессы способствуют неадекватной вентиляционной перфузии и уменьшению эластичности легких [5,8].…”
Section: детской хирургии анестезиологии и реаниматологииunclassified
“…Transmission of thermal energy mostly occurs in the supraglottic airway, whereas chemical irritants in smoke affect the lower airways and lung parenchyma. 4 , 7 …”
mentioning
confidence: 99%
“…8,9 Several studies have demonstrated high levels of proinflammatory, procoagulant, and antifibrinolytic biomarkers in bronchoalveolar lavage fluid from the respiratory tracts of patients with IHI. 4,8,[10][11][12] IHI has also been shown to induce systemically measurable effects. Davis et al showed that inflammatory plasma cytokines were present early after injury and correlate with injury severity and mortality.…”
mentioning
confidence: 99%